2014
DOI: 10.1519/jsc.0000000000000265
|View full text |Cite
|
Sign up to set email alerts
|

High School Physical Educators' and Sport Coaches' Knowledge of Resistance Training Principles and Methods

Abstract: The purpose of this study was to determine the level of knowledge that current and preservice high school (HS) physical educators and sport coaches possess regarding the principles and methods involved in youth resistance training (RT) and to determine if that knowledge was acceptable based on a predetermined criterion (passing score). A panel of 10 experts in RT or sport pedagogy used a Delphi technique to create a 90-question assessment (examination) that was administered to 287 HS physical educators and spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…Extreme conditioning protocols which include exhaustive metabolic resistance training programmes have been found to alter barbell back squat biomechanics and injury risk in trained adults76 and therefore this type of training would not be expected to favour optimal strength development in youth with limited resistance training experience. The development of a standard certification related to youth strength and conditioning is warranted 74 77…”
Section: Survival Of the Strongestmentioning
confidence: 99%
“…Extreme conditioning protocols which include exhaustive metabolic resistance training programmes have been found to alter barbell back squat biomechanics and injury risk in trained adults76 and therefore this type of training would not be expected to favour optimal strength development in youth with limited resistance training experience. The development of a standard certification related to youth strength and conditioning is warranted 74 77…”
Section: Survival Of the Strongestmentioning
confidence: 99%
“…For example, recently, it has been shown dized approach to school-based physical education should that high school physical education teachers' and youth offset the chances of exposing youth to isolated blocks of sport coaches' knowledge and understanding of youth resis-HRE that fails to produce long-term gains above and tance training is deficient and not consistent with the recbeyond that of growth and maturation. ommended guidelines (39,70). Consequently, it is imperative Of interest to the practitioner is how philosophies from that physical education teacher training programs provide athletic development modeling ( 5 8 ) can be integrated within trainee teachers with the relevant curriculum to ensure that, school-based physical education.…”
Section: Problem 5: Current Physical Education Provisionmentioning
confidence: 99%
“…Resistance training for youth is becoming more prevalent in high schools as the safety and benefits of this type of training are gaining acceptance (42). However, there is a clear lack of specific guidance on programming for youth (57). A survey showed that high school physical education teachers and sport coaches, as well as university physical education students, may lack the required knowledge and experience to design, implement and supervise youth resistance training programs (57).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a clear lack of specific guidance on programming for youth (57). A survey showed that high school physical education teachers and sport coaches, as well as university physical education students, may lack the required knowledge and experience to design, implement and supervise youth resistance training programs (57). Therefore, the purpose of this article is to provide coaches and educators an example of how resistance training can be effectively implemented into secondary-school curriculum, as well as highlight some of the challenges faced by coaches operating in the high school setting.…”
Section: Introductionmentioning
confidence: 99%